Effects of some physical agents on Staphylococcus epidermidis and Leishmania tropica: An In vitro study - Al-Waeli, Farah Mahmood Shtaib (Iraqi Journal of Science, 2018)
This work evaluated the effect of Alpha, Gamma irradiation and Nd:YAG, He-Ne laser on Staphylococcus epidermidis and Leishmania tropica in vitro. The experiment included five replicate of S. epidermidis , L. tropica in vitro exposed to effect of Alpha , Gamma irradiation by 241Am isotopes , in two doses